2019
DOI: 10.1016/j.bbalip.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Omega 3 rich diet modulates energy metabolism via GPR120-Nrf2 crosstalk in a novel antioxidant mouse model

Abstract: With obesity rates reaching epidemic proportions, more studies concentrated on reducing the risk and treating this epidemic are vital. Redox stress is an important metabolic regulator involved in the pathophysiology of cardiovascular disease, Type 2 diabetes, and obesity. Oxygen and nitrogenderived free radicals alter glucose and lipid homeostasis in key metabolic tissues, leading to increases in risk of developing metabolic syndrome. Oxidants derived from dietary fat differ in their metabolic regulation, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 133 publications
1
12
0
Order By: Relevance
“…In addition to regulation by GLP-1R, evidence suggests that ω-3 PUFAs, such as DHA, could activate Nrf2-ARE signaling directly [96][97][98]. Moreover, recent studies propose that the activation of GPR120 could increase Nrf2 levels [99,100]. Furthermore, greater nigral dopaminergic neuron loss and more prominent dystrophic dendrites are found in Nrf2 knockout animals following αSyn injection in the ventral midbrain [101].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulation by GLP-1R, evidence suggests that ω-3 PUFAs, such as DHA, could activate Nrf2-ARE signaling directly [96][97][98]. Moreover, recent studies propose that the activation of GPR120 could increase Nrf2 levels [99,100]. Furthermore, greater nigral dopaminergic neuron loss and more prominent dystrophic dendrites are found in Nrf2 knockout animals following αSyn injection in the ventral midbrain [101].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NRF2 activity can be modified by daily consumption of specific food and phytochemicals. Most of these micronutrients/compounds are contained in plant-based food such as kaempferol (a polyphenol found in some fruits and vegetables), niga-ichigoside (a triterpenoid saponin from rosacea), salacia chinensis extracts (a climbing plant that contains triterpenes, phenolic compounds, and glycosides), hydroxytyrosol (the main phenolic compound in olives), curcumin, rebaudioside (a sweetener from Stevia rebaudiana), chicoric acid, and omega 3 and polyunsaturated fatty acids [ 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 ]. In addition, NFE2L2 gene expression can be upregulated by fibre-enriched diets [ 179 ].…”
Section: Nrf2 and Brain (Dys)functionsmentioning
confidence: 99%
“…Studies by Ik Dong Yoo et al have shown that overexpression of Clock and Bmal1 significantly inhibited aerobic sulfation and lactic acid production by reducing the protein expression levels of hexokinase 1 (HK1) and lactate dehydrogenase A (LDHA) [ 176 ]. Redox stress is an important metabolic regulation factor [ 177 ]. Circadian rhythm disorders alter a variety of proteins that are known to regulate glucose stability and/or energy metabolism and are involved in changes in metabolic physiology.…”
Section: The Circadian Clock Regulates Energy Metabolismmentioning
confidence: 99%